New purine alkaloids from the Red Sea marine tunicate Symplegma rubra. (September 2015) - Youssef, Diaa T.A.; Mohamed, Gamal A.; Shaala, Lamiaa A.; Badr, Jihan M.; Bamanie, Faida H.; Ibrahim, Sabrin R.M.
Graphical abstract: Highlights: The MeOH/CH2 Cl2 (1:1) fraction of the Red Sea tunicate Symplegma rubra was investigated. Four new and six known compounds were isolated. Their structures were established by different spectroscopic analyses. The protein kinase inhibitory activity of the isolated compounds against different kinases was evaluated. Abstract: Investigation of the Red Sea marine tunicate Symplegma rubra Monniot, 1972 gave three new purine alkaloids namely 6-methoxy-7, 9-dimethyl-8-oxoguanine (1 ), 6-methoxy-9-methyl-8-oxoguanine (2 ), and 2-methoxy-7-methyl-8-oxoadenine (4 ) together with seven known compounds: 6-methoxy-7-methyl-8-oxoguanine (3 ), 9-methyl-8-oxoadenine (5 ), 7-methyl-8-oxoadenine (6 ), 8-oxoadenine (7 ), 3-methylxanthine (8 ), inosine (9 ), and homarine (pyridinium-2-carboxylic acid-1-methyl) (10 ). Compound6 was reported here for the first time from a natural source. The structure determination of the compounds was accomplished by extensive interpretation of their spectroscopic data including 1D ( 1 H and 13 C) and 2D ( 1 H– 1 H COSY, HSQC, and HMBC) NMR and high-resolution mass spectral data. The isolated compounds were evaluated for their protein kinase inhibitory activity against different kinases (CDK5, CK1, DyrK1A, and GSK3) at 10 μg/mL. The compounds showed moderate activity against these kinases.